The potential of combined shear wave and strain elastography to reduce unnecessary biopsies in breast cancer diagnostics – An international, multicentre trial. (January 2022) - Golatta, Michael; Pfob, André; Büsch, Christopher; Bruckner, Thomas; Alwafai, Zaher; Balleyguier, Corinne; Clevert, Dirk-André; Duda, Volker; Goncalo, Manuela; Gruber, Ines; Hahn, Markus; Kapetas, Panagiotis; et al.
Abstract: Background: Shear wave elastography (SWE) and strain elastography (SE) have shown promising potential in breast cancer diagnostics by evaluating the stiffness of a lesion. Combining these two techniques could further improve the diagnostic performance. We aimed to exploratorily define the cut-offs at which adding combined SWE and SE to B-mode breast ultrasound could help reclassify Breast Imaging Reporting and Data System (BI-RADS) 3-4 lesions to reduce the number of unnecessary breast biopsies. Methods: We report the secondary results of a prospective, multicentre, international trial (NCT02638935). The trial enrolled 1288 women with BI-RADS 3 to 4c breast masses on conventional B-mode breast ultrasound. All patients underwent SWE and SE (index test) and histopathologic evaluation (reference standard). Reduction of unnecessary biopsies (biopsies in benign lesions) and missed malignancies after recategorising with SWE and SE were the outcome measures. Results: On performing histopathologic evaluation, 368 of 1288 breast masses were malignant. Following the routine B-mode breast ultrasound assessment, 53.80% (495 of 920 patients) underwent an unnecessary biopsy. After recategorising BI-RADS 4a lesions (SWE cut-off ≥3.70 m/s, SE cut-off ≥1.0), 34.78% (320 of 920 patients) underwent an unnecessary biopsy corresponding to a 35.35% (320 versus 495) reduction of unnecessary biopsies. Malignancies in the new BI-RADS 3 cohort were missed in 1.96% (12 of 612 patients). Conclusion: Adding combined SWE and SE to routine B-mode breast ultrasound to recategorise BI-RADS 4a patients could help reduce the number of unnecessary biopsies in breast diagnostics by about 35% while keeping the rate of undetected malignancies below the 2% ACR BI-RADS 3 definition. Highlights: We defined cut-offs for shear wave elastography (SWE) and strain elastography (SE). With B-mode ultrasound, 54% (495 of 920) received an unnecessary breast biopsy. With SWE and SE, only 34.8% (320 of 920) received an unnecessary breast biopsy. BI-RADS 4a patients can be spared a biopsy if SWE and SE indicate a benign lesion. The number of unnecessary biopsies was reduced by approximately 35% (320 versus 495).